ANALISIS BERPIKIR KRITIS SISWA KELAS V PADA MATERI GEOMETRI DENGAN TEKNIK SCAFFOLDING - Ratna Widyaningrum, Ema Butsi Prihastari (Widya Wacana: Jurnal Ilmiah, 2015)
Making decisions and answering correct answers affect to the steps of solving problems, and it isa critical category. Teachers in Ar-Ridho nature school have not made the question of how tomeasure critical thingking skills and abilities to the geometry theory. So that it is requiredscaffolding technique. The research aims to describe the increase of critical thingking skills to thegeometry theory by using scaffolding technique. The subject of the research is grade 5B.Instrumens of the research are CTQ test, observation, and interview. The technique of dataanalysis is mean score, linier regression, and n-gain. The result of the research are 1) there is apositive correlation between skills and abilities of critical thingking which shows 63,4% 2) thelevel of critical thingking skillsof the chosen subject increases by the medium category as 0,43.Keyword: critical thingking, geometry, scaffolding technique